IMF Research Bulletin, December 2008. (IMF Research Bulletin; IMF Research Bulletin, 2008)
December 2008: IMF research summaries on global herding in financial markets (by Marco Cipriani) and on fiscal decentralization (by Lusine Lusinyan); article on the experiences of IMF staff at the Nobel Laureate Meetings in Lindau, Germany (by Chris Crowe); listing of visiting scholars at the IMF during August-December 2008; listing of contents of Vol. 55 No. 4 of IMF Staff Papers; listing of recent IMF Working Papers; listing of recent external publications by IMF staff; and a Call for Papers for an upcoming conference on structural reforms.